2016
DOI: 10.1128/jcm.00238-16
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Analysis of NS3/4A, NS5A, and NS5B Genes from Patients Infected with Hepatitis C Virus Genotypes 5 and 6

Abstract: Direct-acting antivirals (DAAs) with activity against multiple genotypes of the hepatitis C virus (HCV) were recently developed and approved for standard-of-care treatment. However, sequencing assays to support HCV genotype 5 and 6 analysis are not widely available. Here, we describe the development of a sequencing assay for the NS3/4A, NS5A, and NS5B genes from HCV genotype 5 and 6 patient isolates. Genotype-and subtype-specific primers were designed to target NS3/4A, NS5A, and NS5B for cDNA synthesis and nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The HCV genotype 4‐specific method, Ref084, covered all key DAA RASs and reported the most in‐depth validation of all genotype 4‐specific methods identified. The HCV subtype 5a‐specific method, Ref035, covered all key DAA RASs and was the only method specific for genotype 5 that was identified. No methods covering all DAA RASs in NS5A designed to amplify genotype 6 were identified.…”
Section: Summary Of Available Literaturementioning
confidence: 99%
“…The HCV genotype 4‐specific method, Ref084, covered all key DAA RASs and reported the most in‐depth validation of all genotype 4‐specific methods identified. The HCV subtype 5a‐specific method, Ref035, covered all key DAA RASs and was the only method specific for genotype 5 that was identified. No methods covering all DAA RASs in NS5A designed to amplify genotype 6 were identified.…”
Section: Summary Of Available Literaturementioning
confidence: 99%
“…A total of 1026 records were excluded after scanning titles and abstracts. As a result, 49 full-text articles were subjected to detailed evaluation, of which, in one study, patients were coinfected with HIV [7] ; 4 papers were review articles [8–11] ; 2 studies did not include patients infected with genotype 6 HCV [12,13] ; 1 study had a smaller sample size than the other study from the same region with the same topic [14] ; 10 studies did not have relevant outcomes [13,15–23] ; 6 studies were repeat reports [24–28] ; 8 studies included <10 patients infected with genotype 6 HCV. [29–35] Finally, 7 randomized-controlled trials and 10 cohorts were chosen for inclusion in the meta-analysis, which comprised a total of 3343 patients.…”
Section: Resultsmentioning
confidence: 99%
“…A LDV/SOF trial by Gane et al found NS5A baseline polymorphism in all GT6 patients but negative in a patient who experienced virologic relapse, who instead, had NS5B variant S282T (polymorphism that is associated with resistance to SOF) detected at the time of relapse. Both NS3 and NS5A RASs were found in a patient who experienced virologic breakthrough in a study by Asselah et al (T93A in NS3 sequence and A156M in NS5A sequence, which were both associated with resistance to PIB and GLE respectively), yet high SVR rates were noted in these trials . Thus, based on the limited data available, baseline RASs seems to be common but minimally impact treatment outcome in GT6 patients.…”
Section: Discussionmentioning
confidence: 97%